Clinical Utility of Pharmacogene Panel‐Based Testing in Patients Undergoing Percutaneous Coronary Intervention. Issue 3 (16th January 2020) - El Rouby, Nihal; Alrwisan, Adel; Langaee, Taimour; Lipori, Gloria; Angiolillo, Dominick J; Franchi, Francesco; Riva, Alberto; Elsey, Amanda; Johnson, Julie A.; Cavallari, Larisa H.; Winterstein, Almut G.
Abstract : We aimed to estimate the utility of panel‐based pharmacogenetic testing of patients undergoing percutaneous coronary intervention (PCI). Utilization of Clinical Pharmacogenetic Implementation Consortium (CPIC) level A/B drugs after PCI was estimated in a national sample of IBM MarketScan beneficiaries. Genotype data from University of Florida (UF) patients ( n = 211) who underwent PCI were used to project genotype‐guided opportunities among MarketScan beneficiaries with at least one ( N = 105, 547) and five ( N = 12, 462) years of follow‐up data. The actual incidence of genotype‐guided prescribing opportunities was determined among UF patients. In MarketScan, 50.0% (52, 799/105, 547) over 1 year and 68.0% (8, 473/12, 462) over 5 years had ≥ 1 CPIC A/B drug besides antiplatelet therapy prescribed, with a projected incidence of genotype‐guided prescribing opportunities of 39% at 1 year and 52% at 5 years. Genotype‐guided prescribing opportunities occurred in 32% of UF patients. Projected and actual incidence of genotype‐guided opportunities among two cohorts supports the utility of panel‐based testing among patients who underwent PCI.